1967
DOI: 10.4141/cjps67-126
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Ethylene Levels in the Atmosphere of Small Containers of Apples

Abstract: not available

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1

Year Published

1978
1978
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 0 publications
0
9
1
Order By: Relevance
“…Subsequent samples contained an appreciable amount of ethylene. The incomplete removal of ethylene by brominated activated charcoal (7,20) and permanganates (7) reported in previous studies, as compared to our results (methods 12, 14, and 15), could be a consequence of different surface to volume ratios and different initial amounts of ethylene. Iodine pentoxide (method 16) oxidized ethylene as well as most of ethane.…”
Section: --12contrasting
confidence: 36%
“…Subsequent samples contained an appreciable amount of ethylene. The incomplete removal of ethylene by brominated activated charcoal (7,20) and permanganates (7) reported in previous studies, as compared to our results (methods 12, 14, and 15), could be a consequence of different surface to volume ratios and different initial amounts of ethylene. Iodine pentoxide (method 16) oxidized ethylene as well as most of ethane.…”
Section: --12contrasting
confidence: 36%
“…Potassium permanganate is a stable purple solid that is a strong oxidizing agent and readily oxidizes ethylene. The ability of potassium permanganate to reduce ethylene concentration in the atmosphere around horticultural produce was fi rst demonstrated by Forsyth et al (1967) on apples. The reduction in ethylene affected by addition of potassium permanganate was subsequently found to delay the ripening of many climacteric fruits such as banana (Scott et al, 1970), kiwifruit (Scott et al, 1984), mango (Esguerra et al, 1978) and avocado (Hatton and Reeder, 1972).…”
mentioning
confidence: 99%
“…Accepted for publication 12 Dec. 2003. as celite (Forsyth et al, 1967), vermiculite (Scott et al, 1970), alumina (Jayamaran and Raju, 1992), zeolite (Oh et al, 1996) and clay (Picon et al, 1993). A range of commercial potassium permanganate products is now available with a common carrier being alumina beads (e.g., Purafi l (Purafi l, Doraville Ga.), Circul-Aire (Circul-Aire, Montreal), Ethysorb (Molecular Products, Thaxted, Essex) and Bloomfresh (Ausdel, Cheltenham, Victoria)).…”
mentioning
confidence: 99%
“…One of the simplest ways to remove ethylene from the atmosphere is to absorb and oxidize it with potassium permanganate to produce CO 2 and H 2 O. The ability of potassium permanganate in reducing the ethylene concentration in the atmosphere around horticultural produce was first demonstrated by Forsyth et al (1967) in apples. It was demonstrated that KMnO 4 retarded the ripening of many fruits (Scott et al 1970;Wills et al 1989).…”
Section: Introductionmentioning
confidence: 99%